2001
DOI: 10.1128/iai.69.6.3646-3651.2001
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for Fc on the Surfaces of Schistosomes

Abstract: Schistosoma mansoni masks its surface with adsorbed host proteins including erythrocyte antigens, immunoglobulins, major histocompatibility complex class I, and ␤ 2 -microglobulin (␤ 2 m), presumably as a means of avoiding host immune responses. How this is accomplished has not been explained. To identify surface receptors for host proteins, we biotinylated the tegument of live S. mansoni adults and mechanically transformed schistosomula and then removed the parasite surface with detergent. Incubation of bioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 43 publications
8
81
0
2
Order By: Relevance
“…Thus, if schistosomes possess endogenous Fc receptors they will only be identified by functional studies. Indeed the muscle protein paramyosin has been proposed as an Fc receptor in Schistosoma japonicum (32) and reported at the tegument surface by immunofluorescent staining (33) but was not detected in this or our previous study on the S. mansoni surface (14). The presence of IgM at the surface, for which no Fc receptor has been described in schistosomes, may indicate binding to specific antigens via the Fab region.…”
Section: Table I Properties Of the Two Biotinylation Reagents Used Tomentioning
confidence: 55%
See 1 more Smart Citation
“…Thus, if schistosomes possess endogenous Fc receptors they will only be identified by functional studies. Indeed the muscle protein paramyosin has been proposed as an Fc receptor in Schistosoma japonicum (32) and reported at the tegument surface by immunofluorescent staining (33) but was not detected in this or our previous study on the S. mansoni surface (14). The presence of IgM at the surface, for which no Fc receptor has been described in schistosomes, may indicate binding to specific antigens via the Fab region.…”
Section: Table I Properties Of the Two Biotinylation Reagents Used Tomentioning
confidence: 55%
“…This may explain why we failed to detect the glucose transporter SGTP4 when others using a similar protocol to biotinylate the worm surface and recover tagged proteins were able to locate it on a blot using specific antibody (30). We also failed to detect SmRK-1, a member of the transforming growth factor-␤ family of receptor kinases, reported previously as labeled by sulfo-NHS-LC biotin (15,31), and SCIP-1 (paramyosin), proposed both as an Fc receptor (32) and as an inhibitor of complement C9 polymerization (33).…”
Section: Table I Properties Of the Two Biotinylation Reagents Used Tomentioning
confidence: 58%
“…It has also been found to be an immunogen during infection of mice and humans with helminth parasites (27,37,47). A nonfilamentous membrane-bound form of paramyosin was also found in the tegumental outer layer (16,33) and on the surface (18,31) of S. mansoni schistosomes. Analyzed on the basis of its capacity to bind to Fc (31), it has been suggested to have immunomodulatory activities.…”
mentioning
confidence: 92%
“…They involved in immunological defense mechanism of parasites by acting as Fc receptors [17,18] and induced allergenic responses in humans [19]. These results suggested that paramyosin of helminth parasites are multifunctional proteins acting not only as structural protein in muscle layers to control their contraction physiologically, but also as an immunoregulatory molecule interacting with the host immune system.…”
Section: Introductionmentioning
confidence: 99%